Numerical methods and parallel algorithms for computation of periodic responses of plates - Stoykov, S.; Margenov, S. (Journal of computational and applied mathematics, 2017)
Numerical methods that compute the nonlinear frequency–response curves of plates are presented. The equation of motion of the plate is derived by assuming first order shear deformation theory and considering geometrical type of nonlinearity. It is discretized by the finite element method using bilinear quadrilateral elements. The frequency–response curve is computed by shooting and continuation methods. Parallel implementation of the shooting method is presented and its scalability is investigated.